Training of Front Line Staff in Himachal Pradesh - Dhiman, R. C.; Gupta, H. K. (Indian Forester, 2004)
Front Line Staff in Himachal Pradesh is trained in its Forest Training School, ChaiI and Forest Training Centre, Sundarnagar in which there is fairly good developed training infrastructure. This paper provides details of trainees trained so far, their characteristics, training programmes and training needs of the Front Line Staff.